Subtyping and grading of synovial sarcomas: a cyto-histopathologic correlation study - Kaushik, Ankit; Khanna, Geetika; ., Rajni; Yadav, Yogesh Kumar (Annals of Pathology and Laboratory Medicine, 2015)
Introduction: Synovial sarcoma is a mesenchymal spindle cell tumor which displays variable epithelial differentiation, including glandular formation and has a specific chromosomal translocation t(X; 18). Fine-needle aspiration cytology (FNAC) is increasingly accepted as a valid screening technique with high sensitivity and specificity in establishing the presence of malignancy and determining the mesenchymal nature of a lesion. Aims and Objectives: In this present study, cytological features, subtyping and grading were studied retrospectively from the histologically confirmed 14 cases of synovial sarcomas and then subsequently correlated our findings from histology section. Methods: This is a retrospective study conducted in Central Institute of Orthopedic (CIO) laboratory. A total 14 cases with a diagnosis of synovial sarcomas from CIO laboratory from past 4 years were retrieved and reviewed for cytohistological correlation, subtyping and grading of synovial sarcoma. Results: Out of total 14 cases of histological proven synovial sarcomas, 12 cases were exactly subtype on cytology. The cytological grading was only similar in 7 of 13 cases that were graded. Conclusion: FNAC is an important and useful tool in diagnosing and subtyping synovial sarcoma.